The Effect of Meditation on Learning Performance: A Review - Tanantpapat, Tanainan; Thongbor, Anuphap; Kaewrujee, Natthitaporn; Tunchaiyaphum, Surawith; Peechapol, Chattavut (วารสารมนุษยศาสตร์และสังคมศาสตร์ มหาวิทยาลัยเอเชียอาคเนย์, 2023)
This literature review aimed to compile empirical evidence of the effect of meditation on learning performance. Search strategies were conducted using online databases to identify published studies from 2012 to 2022, which are twenty articles that met the selection criteria. The review consisted of data extraction according to the data extraction form and analysis of articles by narrative synthesis to describe the meditation practice and their results in a learning context. Results revealed that meditation had been expressed as positively impacting learning achievement and cognitive skills while reducing anxiety and stress among those who practice. Moreover, the investigation guides further research in designing meditation practices to enhance the learning performance of learners.